It's time to cast your vote for the thinking Yang Berhormat - Abd Razak, Dzulkifli (2004)
THE 2004 election is a "thinking election", according to Royal Professor Ungku Aziz (Sunday Mail, March 14) and his assessment is both frank and fair. Not only is the election in the new milllenium, but it is also the first for a new leadership seeking a fresh mandate. Since taking over the country’s top job, Datuk Seri Abdullah Ahmad Badawi has set Malaysians on a new thinking path towards change and openness. Someone likened the initiatives taken thus far as opening up windows when he steps into a room. By now Malaysians are attuned to some important postelection changes as expected with the new era.